Frequency and Documentation of Medication Decisions on Discharge from the Hospital to Hospice Care. Issue 6 (10th March 2019) - Kadoyama, Kirsten L.; Noble, Brie N.; Izumi, Shigeko; Fromme, Erik K.; Tjia, Jennifer; McPherson, Mary Lynn; Candrian, Carey B.; McGregor, Jessina C.; Ku, In Young; Furuno, Jon P.
Abstract : OBJECTIVES: To quantify the frequency and type of medication decisions on discharge from the hospital to hospice care. DESIGN: Retrospective cohort study. SETTING: A 544‐bed academic tertiary care hospital in Portland, Oregon. PARTICIPANTS: A total of 348 adult patients (age ≥18 y) discharged to hospice care between January 1, 2010, and December 31, 2016. MEASUREMENTS: Data were collected from an electronic repository of medical record data and a manual review of patients' discharge summaries. Our outcomes of interest were the frequency and type of medication decisions documented in patients' discharge summaries. Medication decisions were categorized as continuation, continuation but with changes in dose, route of administration, and/or frequency, discontinuation, and initiation of new medications. We also collected data on the frequency of patient/family in the participation of medication‐related decisions. RESULTS: Patients were prescribed a mean of 7.1 medications (standard deviation [SD] = 4.8) on discharge to hospice care. The most prevalent medications prescribed on discharge were strong opioids (82.5%), anxiolytics/sedatives (62.9%), laxatives (57.5%), antiemetics (54.3%), and nonopioid analgesics (45.4%). However, only 67.8% (213/341) of patients who were prescribed an opioid on discharge to hospice care were also prescribed a laxative. Discharging providers made a mean of 15.0 decisions (SD = 7.2) per patient of which 28.5% were to continue medications without changes, 6.7% were to continue medications with changes, 30.3% were to initiate new medications, and 34.5% were to discontinue existing medications. Patients and/or family members were involved in medication decisions during 21.6% of discharges; patients were involved in 15.2% of decisions. CONCLUSION: Patients averaged more than 15 medication decisions on discharge to hospice care. However, it was rarely documented that patients and/or their families participated in these decisions. J Am Geriatr Soc, 2019.